T cell receptor-triggered nuclear actin network formation drives CD4+ T cell effector functions - Tsopoulidis, Nikolaos; Kaw, Sheetal; Laketa, Vibor; Kutscheidt, Stefan; Stolp-Rastätter, Bettina; Fackler, Oliver Till (Science immunology, 2019)
T cell activation is regulated by numerous mechanisms upon T cell antigen receptor (TCR) engagement, including induction of specific cytokines by transcription factors like NF-κB and NFAT. Tsopoulidis et al. now show that TCR engagement causes rapid nuclear actin polymerization to create a dynamic actin filament network that is critical to CD4+ T cell effector functions.
Im Titel erscheint das + bei der Zeichenfolge CD4+ hochgestellt
Gesehen am 25.01.2019